Tanggung Jawab Dokter Dan Rumah Sakit Terhadap Tindakan Emergency Pembedahan Orthopaedi - Atika Rizka Fajrina; Wahyu Andrianto; Saskia Tuksadiah (Supremasi Hukum: Jurnal Penelitian Hukum, 2021)
This journal discusses the responsibilities of doctors and hospitals in emergency orthopaedic measures. It also discusses the role of informed consent in such measures. The author sharpens this research by analyzing verdict No.11/PDT.G/2015/PN.KWG and No.96/PDT.G/2017/PT.BDG. Problems tackled in this journal include the responsibilities of doctors and hospitals as well as informed consent in orthopaedic emergency measures. Sri Lestari filed a torts lawsuit in the form of malpractice as stipulated in Articles 1365, 1366, and 1367 of the Indonesian Civil Code. Emergency action is said to be against the law if it fulfills the elements in Article 1365 of the Civil Code. Furthermore, to determine whether a doctor and hospital can be held responsible and are obliged to provide compensation, it is essential to discern the relation between the tort done and losses incurred. In this journal, the research method used is normative juridical with descriptive research. From the results of this study, it is suggested that there is a need for supervision from the hospital regarding all medical actions taken by health workers to avoid errors in handling patients.Keywords: Doctor; Hospital; Responsibility; Tort; Tulisan ini membahas tanggung jawab hukum dokter dan rumah sakit serta peranan informed consent dalam tindakan emergency orthopaedi. Penulis menganalisis Putusan No.11/PDT.G/2015/PN.KWG dan No.96/PDT.G/2017/PT.BDG. Dalam putusan tersebut, SL mengajukan gugatan perbuatan melawan hukum terkait malpraktek sebagaimana yang diatur di dalam Pasal 1365, 1366, dan 1367 KUHPerdata. Metode penelitian yang dipergunakan adalah yuridis normatif dengan tipe penelitian, yaitu deskriptif. Untuk dapat dikategorikan perbuatan melawan hukum, maka harus memenuhi unsur-unsur Pasal 1365 KUHPerdata. Selain itu, untuk menentukan seorang dokter dan rumah sakit dapat bertanggung jawab dan memberikan ganti rugi, harus ada hubungan kausalitas antara kesalahan dan kerugian yang ditimbulkan. Dalam putusan ini, dokter dan rumah sakit tidak dapat dimintakan pertanggungjawaban atas kerugian yang diderita oleh SL. Perlu adanya pengawasan dari pihak rumah sakit terhadap segala tindakan medis yang dilakukan oleh tenaga kesehatan untuk menghindari terjadinya kesalahan dalam melakukan penanganan terhadap pasien.Kata kunci: Dokter; Rumah Sakit; Tanggung Jawab; Perbuatan Melawan Hukum;